Religion without God - Billington, Ray (Routledge, 2002)
A criticism of theism, and in particular monotheism, Religion without God questions the assumption that rejecting God means rejecting religion. Drawing on Western philosophical critiques of religion and non-theistic Eastern religions, Ray Billington shows how a religion without God could work. The concept of religion without God has informed not only the theories of Nietzsche, Kant and Spinoza, but also expressions of belief in Indian and Chinese religions-Hinduism, Theravada Buddhism Zen and Taoism. Concluding with a look at the "the future of faith," this is a wide-ranging look at what it means to "have faith" and how this is distinct from religious belief.